Niche cosmetic brands decising making on international expansion - Schörnich, Anna Marie Christel Penelope (2024)
The aim of this thesis is to compare and examine the decision-making of niche beauty brands, in particular; Manufaktura, Nobilis Tilia and Bain de Terre – about their international expansion. The goal of this study is to analyze the strategic considerations and limitations that these companies have in the international market when deciding whether to expand internationally or stay local. Further, this study explores the challenges and opportunities of expanding internationally while taking into account factors including Internationalization theories, Lindner’s Theory of Demand and Trade Pattern, Expansion strategies, and Modes of entry. Using qualitative research, which includes interviews with representatives of the three niche beauty brands, this thesis evaluates how attributes like market trends, competition, and internal capabilities impact their expansion decisions. The study’s findings indicate that niche beauty brands currently do follow an internationalization approach, but dedicate their business efforts to their domestic market first.